2004
DOI: 10.1159/000068520
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ratio of Heart-Type Fatty Acid-Binding Protein to Myoglobin

Abstract: Background: The concentration of heart-type fatty acid-binding protein (hFABP), a promising novel marker for detection of acute or persistent myocardial damage, is significantly influenced by renal clearance and thus has limitations to its usefulness in patients with renal dysfunction. We evaluated whether the serum ratio of hFABP to myoglobin (F/M) might be a useful marker for assessing cardiac damage in hemodialysis patients. Methods: Serum hFABP and myoglobin were measured, and the value of F/M was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“… 89 FABP4 level is significantly higher in females than in males, possibly because of the larger amount of body fat in females than in males since there is an independent and strong correlation between FABP4 level and adiposity. 89 , 90 Consistent with the results of previous studies showing that levels of several FABPs were increased in subjects with renal dysfunction, 84 , 91 , 92 serum FABP4 level was shown to be negatively correlated with estimated glomerular filtration rate in recent studies, 89 , 93 suggesting that FABPs are eliminated from the circulation mainly by renal clearance. We previously showed that FABP4 level in hemodialysis patients with end-stage kidney disease was about 20 times higher than that in controls with normal renal function and was decreased by 57.2% after hemodialysis.…”
Section: Circulating Concentration Of Fabp4 As a Potent Biomarkersupporting
confidence: 87%
“… 89 FABP4 level is significantly higher in females than in males, possibly because of the larger amount of body fat in females than in males since there is an independent and strong correlation between FABP4 level and adiposity. 89 , 90 Consistent with the results of previous studies showing that levels of several FABPs were increased in subjects with renal dysfunction, 84 , 91 , 92 serum FABP4 level was shown to be negatively correlated with estimated glomerular filtration rate in recent studies, 89 , 93 suggesting that FABPs are eliminated from the circulation mainly by renal clearance. We previously showed that FABP4 level in hemodialysis patients with end-stage kidney disease was about 20 times higher than that in controls with normal renal function and was decreased by 57.2% after hemodialysis.…”
Section: Circulating Concentration Of Fabp4 As a Potent Biomarkersupporting
confidence: 87%
“…In the control subjects, FABP4 levels were negatively correlated with estimated glomerular filtration rate (data not shown), which is an index of renal function, as previously reported in DM patients with nephropathy [16]. We previously measured concentrations of FABP3, which is another member of the FABP family known as heart-type FABP (H-FABP), in HD patients [19]. We found the concentration of FABP3 was increased 13.8-fold in HD patients compared to that in control subjects with normal renal function and was reduced by 40% after HD but was still higher than that in control subjects.…”
Section: Discussionsupporting
confidence: 74%
“…2003) and may be because of a staged response of the myocyte to severe falciparum malaria. Moreover, the H‐FABP/myoglobin ratio, proposed to differentiate myocardial from skeletal muscle damage and from elevation of biochemical markers due to renal impairment (Furuhashi et al. 2003), points to myocardial injury.…”
Section: Discussionmentioning
confidence: 99%